Komik: Karya Sastra Bergambar - Soedarso, Nick (Bina Nusantara University, 2015)
Comic book is a literary medium which communicates via images. It has been part of Indonesian culture since a long time. Back to the 9th century, reliefs of Borobudur temple are proves of the early comic culture in Indonesia. Each relief panel of the Borobudur temple was made with a series of sequential scenes that depict many scenes of the 8th century’s daily life in ancient Java and the story of Sudhana and Manohara. It was made with the same principle of any comics nowadays. This article is a literature study with data gathered from both printed and electronic media. Field observation was done as well to obtain concrete data. Based on the result, comics can be categorized by its forms and formats, such as comic strip, comic book, and graphic novel. With stunning images and increasing in genres, comics easily become one of mass culture. Comics had a lowbrow reputation for much of its history, but nowadays it recieves more and more positive recognition and within academia. Its contribution to the field of entertainment, education, and imagination, especially to the young generation, makes comics as one of the important means of communication.